Tratamento térmico do titânio e suas consequências sobre as propriedades físico-químicas e de biocompatibilidade - Macedo, Haroldo Reis Alves de (2012)
The titanium and titanium alloys are widely used as biomaterial in biomedical device and so research have been developed aiming to improve and/or better to understand interaction biomaterial/biological environment. The process for manufacturing of this titanium implants usually involves a series of thermal and mechanical processes which have consequence on the final product. The heat treatments are usually used to obtain different properties for each application. In order to understand the influence of these treatments on the biological response of the surface, it was done, in this work, different heat treatments in titanium and analyzed their influence on the morphology, adhesion and proliferation of the pre-osteoblastic cells (MC3T3-E1). For such heat-treated titanium disks were characterized by optical microscopy, contact angle, surface energy, roughness, microhardness, X-ray diffraction and scanning through the techniques (BSE, EDS and EBSD). For the analysis of biological response were tested by MTT proliferation, adhesion by crystal violet and β1 integrin expression by flow cytometry. It was found that the presence of a microstructure very orderly, defined by a chemical attack, cells tend to stretch in the same direction of orientation of the material microstructure. When this order does not happen, the most important factor influencing cell proliferation is the residual stress, indicated by the hardness of the material. This way the disks with the highest level state of residual stress also showed increased cell proliferation